Knowledge management for competitive advantage during economic crisis - Ordóñez de Pablos, Patricia 1975- (A volume in the advances in business strategy and competitive advantage (ABSCA) book series, 2015)
"This book brings together the various approaches that affect the superiority of a company's organizational performance and the gains they can make over their competitors by focusing on concepts such as organizational learning and intellectual capital"-- Provided by publisher.